Effect of MgO and Fe2O3 dual sintering aids on the microstructure and electrochemical performance of the solid state Gd0.2Ce0.8O2-δ electrolyte in intermediate-temperature solid oxide fuel cells - Liang, Qingwen; Tang, Ping; Zhou, Jing; Bai, Jinghe; Tian, Dan; Zhu, Xiaofei; Zhou, Defeng; Wang, Ning; Yan, Wenfu (Frontiers in Chemistry, 2022)
Solid state electrolytes have been intensively studied in the solid oxide fuel cells (SOFCs). The aim of this work is to investigate the effects of MgO and Fe2O3 dual sintering aids on the microstructure and electrochemical properties of solid state Gd0.2Ce0.8O3-δ (GDC) electrolytes, which are prepared by a sol-gel method with MgO and Fe2O3 addition to the GDC system. It is found that the addition of MgO and Fe2O3 can reduce the sintering temperature, increase densification of the electrolyte and decrease the grain boundary resistance. The 2 mol% MgO and 2 mol% Fe2O3 co-doped GDC (GDC-MF) exhibits the highest grain boundary conductivity. At 400 ℃, the grain boundary conductivity σgb and total conductivity σt of GDC-MF are 15.89 times and 5.56 times higher than those of GDC. The oxygen reduction reaction (ORR) rate at the electrolyte/cathode interface of GDC-MF is 47 % higher than that of GDC. Furthermore, the peak power density of a single cell supported by GDC-MF is 0.45 W·cm-2 at 700 ℃, 36.7% higher than that of GDC. Therefore, the GDC-MF should be a promising electrolyte material for intermediate-temperature solid oxide fuel cells (IT-SOFCs).